Vibration and Stability Analysis Comparison for Nanoshell and Piezoelectric Nanoshell Subjected to Electrostatic Excitation - Kachapi, Sayyid H. Hashemi (Discontinuity, Nonlinearity, and Complexity, 2026)
In current study, vibration and stability analysis comparison of two nanostructures i.e. nanoshell (NS) and piezoelectric nanoshell (PENS) subjected to electrostatic excitation and Visco-Pasternak medium is investigated using the Gurtin--Murdoch surface/interface (S/I) theory. For this analysis, Hamilton's principles, the assumed mode method combined with Lagrange--Euler's and also Complex averaging method combined with Arc-length continuation are used. It can be seen that by changing the surface/interface densities and as a result, increasing or decreasing the system stiffness, the natural frequency can be less or greater than the state without taking into account the S/I effects. In both nanostructures (NS and PENS), considering the surface/interface effects increase the nonlinear behaviour compared with without S/I effects.